2018
DOI: 10.1021/acsami.8b13542
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Porous Prism Arrays Composed of Hybrid Ni–NiO–Carbon as Highly Efficient Electrocatalysts for Overall Water Splitting

Abstract: Searching for an economical and efficient water splitting electrocatalyst is still a huge challenge for hydrogen production. This work reports one-step synthesis of hierarchical porous prism arrays (HPPAs) composed of Ni–NiO nanoparticles embedding uniformly in graphite carbon (Ni–NiO/C HPPAs), which is derived from metal–organic framework (CPO-27-Ni) prism arrays grown on nickel foam (NF). Remarkable features of the prism arrays, synergistic effect of Ni–NiO/C, porous graphite carbon, high conductive NF, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 74 publications
2
29
0
Order By: Relevance
“…With this intention, we focus on the key step of LOM based on our previous studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], a OHfilling pathway, as shown in the following formulas {½O = O-MO 4 → ½V-MO 4 + e − } and {½V-MO 4 + OH − → ½HO ads -MO 4 + e − }, where M, [MO 4 ], and V denote the transition metal B site of perovskite, the surface structure with oxygen vacancies, and O vacancy, respectively. Some studies have demonstrated that OHfilling is thermodynamically favorable in some perovskite and plays a key role in LOER [36].…”
Section: Introductionmentioning
confidence: 99%
“…With this intention, we focus on the key step of LOM based on our previous studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], a OHfilling pathway, as shown in the following formulas {½O = O-MO 4 → ½V-MO 4 + e − } and {½V-MO 4 + OH − → ½HO ads -MO 4 + e − }, where M, [MO 4 ], and V denote the transition metal B site of perovskite, the surface structure with oxygen vacancies, and O vacancy, respectively. Some studies have demonstrated that OHfilling is thermodynamically favorable in some perovskite and plays a key role in LOER [36].…”
Section: Introductionmentioning
confidence: 99%
“…[7] Consequently, it is urgent to develop non-precious metals or earth-abundant elements based electrocatalysts requiring relatively low overpotentials to initiate OER. [8][9][10][11][12] As reported, low-cost transition metals and their derivatives, especially Ni based oxides, [13,14] hydroxides, [15,16] sulfides, [17][18][19] and phosphides [20,21] have been indicated as favorable candidates for water splitting because of their earth abundance and high catalytic performance characteristics. Among these candidates, NiFe layered double hydroxide (LDH) catalysts have been attracting more and more research attention in electrocatalysis because of their special nanostructure, tunable composition, and large specific surface area.…”
Section: Introductionmentioning
confidence: 99%
“…The outstanding electrocatalytic performance of Fe-Ni 2 P@N,P-CNSs toward OER and ORR can be ascribed to the structural and composition features as follows: (i) the strong coupling effect between the well-dispersed Fe-Ni 2 P particles and conductive porous carbon nanosheets, which is facile for the exposure of more active sites (Hu et al, 2016; Lei et al, 2018); (ii) the introduction of N and P in the carbon matrix, by which the electronic structure of the applied carbon support is effectively modified, creates more available defects with enhanced catalytic activity and durability (Huang et al, 2018; Wei et al, 2018); (iii) the large specific surface area of Fe-Ni 2 P@N,P-CNSs, which provides numerous accessible catalytic sites, and endows available infiltration to the electrolyte for effective O 2 bubble evolution and a reductive reaction over the electrode surface (Fu et al, 2018e; Zhou et al, 2018). By taking advantage of these exceptional structural merits and the synergistic effect between the multi-components, the as-prepared Fe-Ni 2 P@N,P-CNSs display impressive catalytic activity and stability toward both OER and ORR.…”
Section: Resultsmentioning
confidence: 99%